Green packaging system based on hybrid zein/inulin nanofibers activated with copper oxide nanoparticles and Foeniculum vulgare essential oil for preservation of fresh beef - Sara Gholizadeh; Ali Ehsani; Sajed Amjadi; Hossein Ahangari; Vahid Panahiazar (Applied Food Research)
In recent years, there has been a notable focus on using eco-friendly active packaging materials for meat products. In this regard, we developed the zein/inulin electrospun nanofibers (NFs) incorporated with copper oxide nanoparticles (CuONPs) and Foeniculum vulgare essential oil (FEO) for the packaging of fresh beef. Various blending proportions of zein and inulin (90:10, 85:15, and 80:20) were initially employed for electrospinning. The optimal sample ratio for incorporating CuONPs and FEO was 90:10 based on the fiber diameter (435 ± 109 nm) and their morphology. The optimum NFs sample exhibited an average fiber diameter of 589 ± 113 nm with a uniform and bead-free morphology. The incorporation of CuONPs and FEO did not significantly impact the thermal properties of the NFs. The co-incorporation of CuONPs and FEO improved the antioxidant and antibacterial properties of NFs. Moreover, the developed NFs exhibited acceptable surface hydrophobicity, crystallinity, and mechanical properties. Finally, the fresh beef packaging study illustrated that the developed active NFs controlled the changes in the pH, oxidation, bacterial load, and total volatile basic nitrogen in fresh beef samples during cold storage.